Pengaruh board characteristic spesifik bank terhadap kebijkan deviden pada Bank Umum Syariah - Faishal, Hanif; Najib, Moh Farid; Mai, Muhamad Umar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to identify the role of board characteristics, which are proxies with board of directors size, female board of directors, and independent board of commissioners in determining dividend payment policies at Islamic Commercial Banks in Indonesia. This research is explanatory in nature, namely research that examines and explains the causal relationship (cause and effect) between variables developed in several hypotheses. The population and sample of this study are all Islamic Commercial Banks (BUS) registered with the Financial Services Authority (OJK) for the period 2010 to 2020. In this study the method used is logistic regression analysis, the analytical tool used is eviews 9. The results show The variable size of the board of directors and Return On Assets (ROA) have a positive and significant effect on the level of Propensity to Pay Dividend (PPD). In the variable of the Women's Board of Directors (FMBD), the independent commissioner (INBC) has a significant negative effect on the Propensity To Pay Dividend (PPD). The Bank Size Variable (BSIZE) has a negative but not significant value on the Propensity To Pay Dividend (PPD). Meanwhile, the Bank Growth variable (GRWH) has an insignificant positive value on the Propensity To Pay Dividend (PPD).